Integration of the Kaleidoscope Model of Policy Change in the Master’s degree program in Agricultural and Applied Economics at the University of Pretoria, South Africa - CGIAR Research Program on Policies, Institutions, and Markets (2020)
The Kaleidoscope Model, a tool that can be used by researchers, practitioners and donors to identify entry points for improving the likelihood of policy change, was included in the curriculum of the Master’s degree in Agricultural and Applied Economics at the University of Pretoria, South Africa. In 2020, 30 students from 11 African countries were trained in the use of the Kaleidoscope Model through this program.